The Influence of Green Marketing, Green Products and Brand Image on Decisions to Purchase Packaged Drinking Water - Kewo, Stella Theodora (International Review of Management and Marketing, 2025)
The increasing concern for environmental sustainability has led to changes in consumer behavior, with more people seeking environmentally friendly products in their purchasing decisions. This study aims to investigate the influence of green marketing, green products, and brand image on the decision to purchase bottled water. This study is a quantitative study with data collected from 126 respondents who manage small businesses that sell bottled water. The questionnaire filling technique is with a Likert scale of 1-5 and the data collected are analyzed using the structural equation modeling method with a partial Least Squares (PLS) approach. By taking an alpha of 5%, the results of the study indicate that green marketing and brand image have a positive effect on the decision to purchase, but green products do not affect the decision to purchase bottled water.